2021
DOI: 10.2174/1573411016999200526133357
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric Methodologies Applied for Determination of Pharmaceuticals

Abstract: BACKGROUND: The development of innovative approaches in drug analysis is a challenging task for medicine, pharmacy, and engineering sciences. For instance, requirement of proper dosage forms in releasing active ingredients is crucial. It is essential to analyze drugs in biological liquids for early diagnosis and treatment purposes. Drug analysis is also of great importance to control the quality of pharmaceutical products, test their efficacy, and develop novel drug formulation. The present review is aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Additionally, acidification of the reaction mixtures with dilute mineral acid (HCl) did not cause fading of the solutions' colors. This observation revealed that the reaction proceeded via irreversible covalent bonding, rather than the possible irreversible charge-transfer reaction between CER, as an electron donor, and the reagents (CHL, BRL, and DCNQ), as electron acceptors [29].…”
Section: Absorption Spectra and Reaction Stoichiometrymentioning
confidence: 95%
“…Additionally, acidification of the reaction mixtures with dilute mineral acid (HCl) did not cause fading of the solutions' colors. This observation revealed that the reaction proceeded via irreversible covalent bonding, rather than the possible irreversible charge-transfer reaction between CER, as an electron donor, and the reagents (CHL, BRL, and DCNQ), as electron acceptors [29].…”
Section: Absorption Spectra and Reaction Stoichiometrymentioning
confidence: 95%
“…This technique sometimes requires the analysis of the spectrum at many wavelengths. Currently, the ratio spectra derivative method makes selecting a measurement wavelength easy and avoids using the zero-crossing technique to read the derivative result [32,33].…”
Section: Open Accessmentioning
confidence: 99%
“…To overcome these limitations of FIA, Ruzicka and Marshall introduced sequential injection analysis (SIA) in 1990 as an alternative flow-through sample-handling and sensing technique which is economical with respect to both sample and reagent consumption in addition to allowing computer control of most manifold and operational parameters [ 13 ]. This flow technique has been successfully applied to the analysis of analytes of pharmaceutical interest [ 14 , 15 , 16 , 17 ]. Since the reagents for the spectrophotometric determination of NACET mentioned above (i.e., NCN, BCA, and BCS) are expensive (e.g., €146 per gram of BCS, Sigma-Aldrich, Burlington, MA, USA), SIA is expected to reduce significantly the cost of analysis compared to FIA.…”
Section: Introductionmentioning
confidence: 99%